Book Reviews (The ecumenical review, 1985)
Book reviewed in this article: Christentum und Weltreligionen: Hinführung zum Dialog mit Islam, Hinduismus und Buddhismus, by Hans Küng, Josef van Ess, Heinrich von Stietencron, Heinz Bechert, Munich & Zürich Tell Us Our Names: Story Theology from an Asian Perspective, by C.S. Song, Maryknoll No Other Name? by Paul F. Knitter Muhammad and the Christian: a Question of Response, by Kenneth Cragg Worlds of Difference, by Martin Palmer and Esther Bisset